Serum Immune System Biomarkers Neopterin and Interleukin-10 Are Strongly Related to Tryptophan Metabolism in Healthy Young Adults. Issue 9 (3rd August 2016) - Deac, Oana M; Mills, James L; Gardiner, Clair M; Shane, Barry; Quinn, Louise; Midttun, Øivind; McCann, Adrian; Meyer, Klaus; Ueland, Per M; Fan, Ruzong; Lu, Zhaohui; Brody, Lawrence C; et al.
Abstract: Background: Changes in tryptophan metabolism through the vitamin B-6–dependent kynurenine pathway have been linked to activation of the immune system. Objective: We hypothesized that blood concentrations of tryptophan and its catabolites were associated with biomarkers relevant to inflammatory processes in healthy noninflamed subjects. Methods: Healthy young adults ( n = 737) aged 18–28 y without any known diseases or clinical evidence of inflammation provided blood samples for analysis of serum tryptophan/kynurenine metabolites, neopterin, C-reactive protein (CRP), and plasma pyridoxal 5′-phosphate (PLP) with LC–tandem mass spectrometry methodologies. A panel of cytokines was measured in serum by using high-sensitivity ELISA assays. Anthropometric and lifestyle data were collected by questionnaire. Multiple linear regression analysis to determine the effect of measured serum cytokine concentrations as predictors of tryptophan metabolites was performed on inverse normal-rank transformations of the data, adjusted for sex, body mass index, smoking, alcohol intake, and contraceptive use in women. Results: Median serum CRP and neopterin concentrations were well below established clinical cutoffs for inflammation. We observed significant positive associations between serum interleukin-10 (IL-10) and serum kynurenine ( P = 0.0002), the kynurenine-to-tryptophan ratio (KTR) ( P = 0.003), 3-hydroxykynurenine ( P = 0.01), and 3-hydroxyanthranilic acid ( P = 0.04). Serum neopterin was positively associated with kynurenine, the KTR (both P < 0.0001), and anthranilic acid ( P = 0.004), and was negatively associated with serum tryptophan ( P = 0.01) and PLP ( P < 0.0001). Serum tumor necrosis factor α was also negatively associated with tryptophan ( P < 0.001). Conclusions: In healthy young adults with no apparent inflammatory conditions, serum tryptophan metabolites are significantly associated with key immune system biomarkers. The observed association between IL-10 and kynurenine is unexpected and suggests that kynurenine-linked mechanisms promoting negative regulation of inflammatory responses are associated with normal immune homeostasis.